A de novo loss-of-function GRIN2A mutation associated with childhood focal epilepsy and acquired epileptic aphasia. - Kai Gao (PLoS ONE, 2017)
OBJECTIVE:N-methyl-D-aspartate receptors (NMDAR) subunit GRIN2A/GluN2A mutations have been identified in patients with various neurological diseases, such as epilepsy and intellectual disability / developmental delay (ID/DD). In this study, we investigated the phenotype and underlying molecular mechanism of a GRIN2A missense mutation identified by next generation sequencing on idiopathic focal epilepsy using in vitro electrophysiology. METHODS:Genomic DNA of patients with epilepsy and ID/DD were sequenced by targeted next-generation sequencing within 300 genes related to epilepsy and ID/DD. The effects of one missense GRIN2A mutation on NMDAR function were evaluated by two-electrode voltage clamp current recordings and whole cell voltage clamp current recordings. RESULTS:We identified one de novo missense GRIN2A mutation (Asp731Asn, GluN2A(D731N)) in a child with unexplained epilepsy and DD. The D731N mutation is located in a portion of the agonist-binding domain (ABD) in the GluN2A subunit, which is the binding pocket for agonist glutamate. This residue in the ABD is conserved among vertebrate species and all other NMDAR subunits, suggesting an important role in receptor function. The proband shows developmental delay as well as EEG-confirmed seizure activity. Functional analyses reveal that the GluN2A(D731N) mutation decreases glutamate potency by over 3,000-fold, reduces amplitude of current response, shortens synaptic-like response time course, and decreases channel open probability, while enhancing sensitivity to negative allosteric modulators, including extracellular proton and zinc inhibition. The combined effects reduce NMDAR function. SIGNIFICANCE:We identified a de novo missense mutation in the GRIN2A gene in a patient with childhood focal epilepsy and acquired epileptic aphasia. The mutant decreases NMDAR activation suggesting NMDAR hypofunction may contribute to the epilepsy pathogenesis.